Antidepressant-Like Activity of Methanolic Extract From Old Areca Nut Using Forced Swim Test Method In Mice (Mus Musculus) Tested Independently - Riryn Novianty; Nery Sofyanti; Fitra Audhi Ya’la (Jurnal Inovasi Pendidikan dan Sains, 2024)
This study aims to investigate the potential of methanolic extract from aged areca nut as an antidepressant using acute and sub-chronic Forced Swim Test (FST) methods. In the acute FST, mice were injected with methanolic extract doses of 10, 50, and 100 mg/kg intraperitoneally as a single dose to determine the dose with the best activity. Meanwhile, in the sub-chronic FST, the best dose was administered for 7 consecutive days, and a re-test was conducted on the seventh day after acute FST. A significant reduction in immobility time after acute treatment was only observed with a dose of 100 mg/kg. Therefore, mice were injected with this dose for the next 7 days. However, this dose did not significantly decrease immobility time based on the results of sub-chronic FST. Thus, the methanolic extract at a dose of 100 mg/kg was considered not potentially effective for continuous use. Phenolic compounds, steroids, and saponins as the main constituents in the extract did not induce toxic effects after treatment for 7 days.